Stroke care in 17 Sub-Saharan African countries: the FEBRUARY study (2016–2021) from African research network. (3rd October 2022) - Limbole, E; Mipinda, J B; Cavagna, P; Hermann, Y; Tchuem Tchuente-Noutchogouin, M; Souleymane, C; Asselin, A; Mbaye, A; Kamdem, F; Sidy Ali, A; Thiam, S; N'da N'kenon Watani, J; et al.
Abstract: Background: Stroke is one of the leading causes of morbidity and mortality worldwide. Approximately 70% of deaths from stroke and 87% of stroke-related disability would occur in low- and middle-income countries. Between 2002 and 2020, estimation stroke mortality in Sub-Saharan Africa (SSA) was tripled. There is scarce data on management of stroke in SSA. Purpose: To describe stroke care in cardiology departments in 17 SSA countries Methods: We conducted a transversal and longitudinal study in CV department of 37 hospitals from 23 cities in 17 SSA countries (10 low income: Niger, Guinea, Benin, Mali, Democratic Republic of the Congo (DCR), Tchad, Burkina Faso, Togo, Burundi, Ethiopia and 7 middle income: Cote d'Ivoire, Senegal, Cameroon, Congo, Soudan, Mauritania, Gabon). The FEBRUARY study was designed by a multidisciplinary collaborative team of epidemiologists, pharmacists and cardiologists from Africa and France. This ongoing observatory included all inpatients in February from each year since 2016. Data including socio-demographic and clinical characteristics, causes of admission, clinical, biological, complementary examinations, treatments, length of stay and discharge diagnosis were collected by the investigating physicians. All analyses were performed through scripts developed in the R software (4.0.3 (2020-10-10)). Results: Overall, 4360 patients were admitted to hospital over the 6 years of the study. Stroke was the third cause of hospitalization with 477 (11%) patients admitted. Proportions of patients admitted for stroke varied across countries from 0% in Ethiopia to 52% in DRC (p<0.01) (figure) and over the years from 11% in 2016 to 16.5% in 2021. Men represented 60.1% of stroke patients. Mean of age was 62.5±13.4 years. Overall, 300 patients (62.9%) were from low-income countries and 177 patients (37.1%) from middle-income countries. A majority of patients were living in urban areas (N=387; 82.9%) compared to rural areas (N=80; 17.1%). Individual wealth index was low, middle and high in 105 (23.2%), 152 (33.6%) and 196 (43.3%) patients respectively. Among stroke patients, 413 (89.8%) had a computed tomography. Ischemic stroke represented 71.8% of patients with stroke. Among CV risk factors, high blood pressure was identified in 81.9% of patients. In-hospital antithrombotic therapy was prescribed for 2 patients (0.42%). Anticoagulant therapy and antiplatelet therapy were prescribed for 26.4% and 53.5% of patients respectively. Proportions of patients treated with antiplatelet therapy varied across countries (p<0.05). At discharge, 8% and 44.4% of patients received anticoagulant therapy or antiplatelet therapy respectively. Mean of length of stay was 12.4±18.4 days. Stroke represent the second cause of mortality (18.7%) and did not vary significantly across countries. Conclusion: Stroke was the third cause of admission with more than 1/10 patients and the second cause of mortality with almost 1/5 patients in cardiology departments in SSA. Funding Acknowledgement: Type of funding sources: None.